Sinergi kemanunggalan dalam pemulihan sarana pendidikan pasca-bencana hidrometeorologi: Program Latsitardanus XLVI di SDN 1 Tualang Cut, Aceh Tamiang - Muhammad Adrian Rezki Anggara Musnawar Syafei; Gunaryo Gunaryo; Anggi Khairina Hanum Hasibuan; Aura Puja Lestari (CV Rezki Media, 2026)
The 46th Taruna Wreda Nusantara Integration Exercise (Latsitardanus XLVI) in 2026 is an annual national event strategically focused on the restoration of educational facilities following hydrometeorological disasters in Aceh Tamiang Regency, involving a total of 1,980 personnel, comprising 902 cadets from the Indonesian National Defense Academy (510 Military Academy cadets, 238 Naval Academy cadets, and 154 Air Force Academy cadets), 283 Police Academy cadets, 45 SSN Polytechnic cadets, 292 Universitas Pertahanan Republik Indonesia student cadets, and supported by 458 support personnel. Using an integrated crisis management approach divided into pre-implementation, implementation, and evaluation phases, this initiative prioritized the rehabilitation of Public Elementary School 1 Tualang Cut through classroom restoration, environmental cleanup, and the repair of learning facilities to foster cross-institutional collaboration and cultivate a leadership spirit focused on community service. With an effectiveness rate of 90%, this program successfully achieved its recovery targets optimally within the available timeframe, which not only strengthened the bond between cadets and the people and provided moral support to affected residents, but also equipped future officers with professional experience grounded in integrity while upholding the spirit of nationalism as public servants.